Effect of Te substitution on crystal structure and transport properties of AgBiSe2 thermoelectric material. Issue 8 (31st January 2018) - Goto, Y.; Nishida, A.; Nishiate, H.; Murata, M.; Lee, C. H.; Miura, A.; Moriyoshi, C.; Kuroiwa, Y.; Mizuguchi, Y.
Abstract : Reduced lattice thermal conductivity of Te-substituted AgBiSe2 was qualitatively described using the point defect scattering model. Abstract : Silver bismuth diselenide (AgBiSe2 ) has attracted much attention as an efficient thermoelectric material, owing to its intrinsically low lattice thermal conductivity. While samples synthesized using a solid-state reaction showed n-type conductivity and their dimensionless figure of merit ( ZT ) reached ∼1 by electron doping, theoretical calculations predicted that a remarkably high thermoelectric performance can be achieved in p-type AgBiSe2 . In this paper, we present the effect of Te substitution on the crystal structure and thermoelectric properties of AgBiSe2, expecting p-type conductivity due to the shallowing of the energy potential of the valence band. We found that all AgBiSe2− x Te x ( x = 0–0.8) prepared using a solid-state reaction exhibits n-type conductivity from 300 to 750 K. The room-temperature lattice thermal conductivity decreased to as low as 0.3 W m −1 K −1 by Te substitution, which was qualitatively described using the point defect scattering model for the solid solution. We show that ZT reaches ∼0.6 for x = 0.8 at a broad range of temperatures, from 550 to 750 K, due to the increased power factor, although the carrier concentration has not been optimized yet.